2021
DOI: 10.1111/jvs.13040
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific trends and variability in plant functional traits across a latitudinal gradient in northern Alaska

Abstract: Questions Many studies explore how plant functional traits may change as the climate warms by observing traits over environmental gradients. The amount of intraspecific variation (ITV), however, is often unknown and unaccounted for in most trait‐based studies. Our objectives are to: (a) determine if species‐level patterns across a latitudinal gradient match those of other members within the same growth form; (b) compare distributions of trait values across regions; and (c) quantify the amount of ITV within eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 100 publications
2
10
0
Order By: Relevance
“…It is therefore expected to increase with temperature. However, leaf economic traits have been found to both increase and decrease along latitudinal and elevation gradients in arctic tundra ecosystems (Betway et al, 2021;Kudo et al, 2001). For example, Betway et al (2021) found that SLA of Salix pulchra increased from north to south, while Betula nana decreased.…”
Section: Determinants Of Above-and Below-ground Trait Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore expected to increase with temperature. However, leaf economic traits have been found to both increase and decrease along latitudinal and elevation gradients in arctic tundra ecosystems (Betway et al, 2021;Kudo et al, 2001). For example, Betway et al (2021) found that SLA of Salix pulchra increased from north to south, while Betula nana decreased.…”
Section: Determinants Of Above-and Below-ground Trait Variationmentioning
confidence: 99%
“…However, leaf economic traits have been found to both increase and decrease along latitudinal and elevation gradients in arctic tundra ecosystems (Betway et al, 2021;Kudo et al, 2001). For example, Betway et al (2021) found that SLA of Salix pulchra increased from north to south, while Betula nana decreased. One potential explanation for these discrepancies is that the communities or sites where the species occur differ in soil moisture (Baruah et al, 2017;Betway et al, 2021).…”
Section: Determinants Of Above-and Below-ground Trait Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, for the sake of operability and to facilitate integration of data into large databases (e.g., Bocci, 2015), traits are often simplified and treated as spatially constant and invariable within species, whereas bioindicator values may vary among regions based on available expertise and the criteria used. Even if we ignore phenotypic plasticity and intraspecific trait variability (Betway et al, 2021; Kumordzi et al, 2019) and assume that traits vary more between than within species, at least in richer assemblages (Escudero et al, 2021), interactions among traits still add complexity and possible uncertainty to trait‐based predictions of ecological conditions.…”
Section: Introductionmentioning
confidence: 99%